ANALISIS FAKTOR INTERN YANG MEMPENGARUHI HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS XI IPS MAN 1 PONTIANAK - Selpia, Selpia; G.S, Bambang; Rasyid, Rum (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractCommon problem in this research is, internal factor especially on psychological aspect that is learning attitude, interest of learning, and motivation learn that influence student learning result on economy class XI IPS MAN 1 Pontianak ". The general purpose of this study is to find out how the influence of internal factors on student learning outcomes on economic subjects class XI IPS MAN 1 Pontianak. The method used is descriptive method with quantitative approach and survey survey form. The population in this study amounted to 120 students and the sample 55 students. Techniques of data collection using questionnaire (Questionnaire) and observation. While the technique of data analysis using simple linear regression. . The result of the research with the formulation Y '= 77,045 + 1,014X, shows the influence of internal factors on student learning outcomes in the economic subjects of class XI IPS MAN 1 Pontianak. Based on calculations using SPSS v.16 application obtained t arithmetic <t table (0.969 <2.306), then Ha rejected and Ho accepted. Therefore R = 0.134, R2 = 0.017 does not meet the requirements of the 0.05 test. So the internal factors (learning attitudes, interest in learning, and motivation to learn) have no effect on learning outcomes. Keyword:  Internal factors (attitude learning,  interest in  learning, motivation  to learn), Learning outcomes